Letter from Major Otto William Geist, Quartermaster to Clark Wissler - Geist, Otto William (1946)
This archival material has been provided for educational purposes. Ball State University Libraries recognizes that some historic items may include offensive content. Our statement regarding objectionable content is available at: https://dmr.bsu.edu/digital/about